Understanding globalization - Schirato, Tony (Sage Publications, 2003)
Reviewing, historicizing and contextualizing contemporary discussions and debates about globalization, this text provides an introduction to the discourses, texts, practices technologies and politics that have been grouped together under the term 'globalization'.